Trade determinants and opportunities for Indian rice: a dynamic panel gravity model perspective - K. Nirmal Ravi Kumar; K. Gurava Reddy; Adinan Bahahudeen Shafiwu; M. Jagan Mohan Reddy (Cogent Economics & Finance, 2024)
The dynamics of international trade play a pivotal role in shaping economic growth and development for nations worldwide. This significance is particularly pronounced in the context of India's agrarian economy. With a substantial portion of its population dependent on agriculture, engaging in global trade presents a myriad of advantages. As a member of the World Trade Organization (WTO), India benefits from a framework that fosters transparent and fair-trade relations, enabling dispute resolution and favourable negotiations. India's agro-climatic diversity grants it a competitive edge in cultivating various agricultural products, predominantly rice. Enabling policies, like Minimum Support Price and subsidies, incentivize farmers, while adherence to international quality standards enhances the acceptance of Indian rice abroad. The gravity model employed in this study to analyze India's rice trade with major importing countries, offers valuable insights into trade dynamics. When delving into specific determinants of trade, the Heckman selection equation proves useful. Factors like Gross Domestic Product (GDP), per capita income, trade history, and exchange rates consistently impact partner selection. The likelihood of choosing a trading partner is influenced by economic compatibility, historical trade relations and WTO membership. Additionally, shared borders and regional affiliations play a role, while economic recessions tend to decrease partner selection due to reduced demand. Examining trade quantity reveals nuanced dynamics. Historical trade interactions, economic indicators and WTO membership consistently influence trade volumes. Larger GDPs, per capita incomes, and populations of trading partners enhance trade prospects, while disparities in income and exchange rate fluctuations impact trade negatively. Importantly, distance remains a key factor affecting trade volume, as logistical complexities and transportation costs influence trade decisions. These findings shed light on trade dynamics, enabling evidence-based policy decisions to enhance trade relationships, boost competitiveness and propel India's rice exports to new heights.
Keywords: C23; F13; F14; O24; 330; Rice exports; Heckmansection model; generalizedleast squares; Poissonpseudo-maximum-likelihood; panel data